Diagnosing cystic fibrosis-related diabetes: current methods and challenges. (2nd July 2016) - Prentice, Bernadette; Hameed, Shihab; Verge, Charles F.; Ooi, Chee Y.; Jaffe, Adam; Widger, John
ABSTRACT: Introduction : Cystic fibrosis-related diabetes (CFRD) is the end-point of a spectrum of glucose abnormalities in cystic fibrosis that begins with early insulin deficiency and ultimately results in accelerated nutritional decline and loss of lung function. Current diagnostic and management regimens are unable to entirely reverse this clinical decline. Areas covered : This review summarises the current understanding of the pathophysiology of CFRD, the issues associated with using oral glucose tolerance tests in CF and the challenges faced in making the diagnosis of CFRD. Medline database searches were conducted using search terms "Cystic Fibrosis Related Diabetes", "Cystic Fibrosis" AND "glucose", "Cystic Fibrosis" AND "insulin", "Cystic Fibrosis" AND "Diabetes". Additionally, reference lists were studied. Expert commentary : Increasing evidence points to early glucose abnormalities being clinically relevant in cystic fibrosis and as such novel diagnostic methods such as continuous glucose monitoring or 30 minute sampled oral glucose tolerance test (OGTT) may play a key role in the future in the screening and diagnosis of early glucose abnormalities in CF.